The great happiness moderation - Andrew E. Clark; Sarah Flèche; Claudia Senik (Institute for the Study of Labor (IZA), 2012)
This paper shows that within-country happiness inequality has fallen in the majority of countries that have experienced positive income growth over the last forty years, in particular in developed countries. This new stylized fact comes as an addition to the Easterlin paradox, which states that the time trend in average happiness is flat during episodes of long-run income growth. This mean-preserving declining spread in happiness comes about via falls in both the share of individuals who declare low and high levels of happiness. Rising income inequality moderates the fall in happiness inequality, and may even reverse it after some point, for example in the US starting in the 1990s. Hence, if raising the income of all does not raise the happiness of all, it will at least harmonize the happiness of all, providing that income inequality does not grow too much. Behind the veil of ignorance, lower happiness inequality would certainly be considered as attractive by risk-averse individuals.
Keywords: D31; D6; I3; O15; 330; happiness; inequality; economic growth; development; Easterlin paradox; Zufriedenheit; Soziale Ungleichheit; Wirtschaftswachstum; Entwicklung; Einkommensverteilung; Welt; Glücksforschung